219k views
2 votes
Please answer, I haven’t no clue how to work it out

Please answer, I haven’t no clue how to work it out-example-1
User Kits
by
4.6k points

2 Answers

6 votes

Answer:

c.)
(x-2)

Explanation:

The given expression is written in the form
ac^2+bx+c. To factor, find two numbers whose sum is b and whose product is c:

_×_=-18

_+_=7

Use -2 and 7:

-2×9=-18

-2+9=7

Substitute the two numbers for b:


x^2-2x+9x-18


(x^2-2x)+(9x-18)

Factor out common terms. The common term in the first parentheses is x and the common term in the second is 9:


x((x^2-2x)/(x) )+9((9x-18)/(9))\\\\x(x-2)+9(x-2)

Cancel out one of the parentheses since they have the same terms and plug the factored numbers in:


(x-2)(x+9)

:Done

Check Your Work:

To see if the given factored form is true, simplify it using FOIL:

First, Outside, Inside, Last


(x-2)(x+9)

Multiply the first terms:


x*x=x^2

Multiply the terms on the outside:


x*9=9x\\\\x^2+9x

Multiply the inside terms:


-2*x=-2x\\\\x^2+9x-2x

Multiply the last terms:


-2*9=-18\\\\x^2+9x-2x-18

Combine like terms:


x^2+(9x-2x)-18\\\\x^2+7x-18

Therefore, the factored form is true.

User Fuglede
by
4.9k points
2 votes

Answer:

C. x-2

Explanation:

x² + 7x - 18 = 0

the factor must be p and q from the form.of

(x+p)(x+q) = 0

then find the value of p and q by this rules

p + q = 7

p x q = -18

p = 9

q = -2

(x + 9)(x + (-2)) = 0

(x+9)(x-2) = 0

User Erik Forbes
by
5.2k points